2016
DOI: 10.17245/jdapm.2016.16.3.217
|View full text |Cite
|
Sign up to set email alerts
|

Use of ADMS™ during sedation for dental treatment of an intellectually disabled patient: a case report

Abstract: Dental treatment is often performed under general anesthesia or sedation when an intellectually disabled patient has a heightened fear of treatment or has difficulty cooperating. When it is impossible to control the patient due to the severity of intellectual disability, conscious sedation is not a viable option, and only deep sedation should be performed. Deep sedation is usually achieved by propofol infusion using the target controlled infusion (TCI) system, with deep sedation being achieved at a slightly lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
7
0
4

Year Published

2019
2019
2021
2021

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 24 publications
0
7
0
4
Order By: Relevance
“…Today, many associations such as the ADA (American Dental Association), ADSA (American Dental Society of Anesthesiology), KDSA (The Korean Dental Society of Anesthesiology), among others, have proposed a series of guidelines for safety procedure of sedation according to the degree of depth and also for anesthesia, these guidelines, the advancement of technology, the amount of information and continuing education for dentists has helped to improve the conditions of private clinics that has allowed the use of outpatient general anesthesia and sedation by highly qualified dentist and fulfilling the requirements according to the guidelines of your country of residence [4]. It has been shown that deep sedation is recommended for disabled patients who are difficult to treat and allows a better management of the patient, since the patient is in a state of reduced body movement and responding only to painful or repeated stimuli, which make the dental treatment comfortable for the dentist as the patient [5].…”
Section: Introductionmentioning
confidence: 99%
“…Today, many associations such as the ADA (American Dental Association), ADSA (American Dental Society of Anesthesiology), KDSA (The Korean Dental Society of Anesthesiology), among others, have proposed a series of guidelines for safety procedure of sedation according to the degree of depth and also for anesthesia, these guidelines, the advancement of technology, the amount of information and continuing education for dentists has helped to improve the conditions of private clinics that has allowed the use of outpatient general anesthesia and sedation by highly qualified dentist and fulfilling the requirements according to the guidelines of your country of residence [4]. It has been shown that deep sedation is recommended for disabled patients who are difficult to treat and allows a better management of the patient, since the patient is in a state of reduced body movement and responding only to painful or repeated stimuli, which make the dental treatment comfortable for the dentist as the patient [5].…”
Section: Introductionmentioning
confidence: 99%
“…17,18) , 비무작위 대조군 임상연구 2편 19,20) , 후향적 차트 리뷰 5편 [21][22][23][24][25] 이 보고되었다. 증례보고는 2편 26,27) , 기타 단 순 보고서나 문헌고찰이 2편 28,29) 보고되었다( Table II).…”
unclassified
“…(2) 연구자 선정된 연구들에서 13편의 연구가 치과 치료 관련 연 구 [17][18][19][20][21][22][23][24][25][26][27][28][29] 였으며, 나머지 11편은 모두 의과 치료 관련 연구 [30][31][32][33][34][35][36][37][38][39][40] 이었다( Table II).…”
unclassified
See 2 more Smart Citations